Business in Great Waters : the U-Boat Wars 1916-1945. - Terraine, John (Pen and Sword, 2009)
Twice within 25 years Britain was threatened with starvation by the menace of the U-Boat. In this study of submarine warfare, the author explains why Winston Churchill wrote ""the only thing that ever frightened me during the war was the U-Boat peril"". Until it had been overcome, the Anglo-American entry into Europe in 1944 would have been impossible. John Terraine concentrates on the combatants themselves, both German and Allied, but does not overlook the three main factors in the equation - the political, the military and the technological, as well as the intelligence, the weapons and the d